The Problem with Appointment of Village Administrator Haya-Haya Village, Limboto,Gorontalo - Roy Marthen Moonti (Universitas Airlangga, 2018)
This paper aims to know how the flow of authority of the village head in appointing Village Administrator in the perspective of Law No. 6/2014 on the Village. This research uses descriptive normative research type. This research was conducted to obtain information, explanation and data on the authority of the Village Head in appointment of Village Administrator in accordance with Law No. 6/2014. The result of the research shows that the procedure of appointment of Village Device In Haya Haya Village, Limboto Sub-district, Gorontalo Regency before the enactment of Law No. 6/2014 was to be decided by the Village Head, but after the enactment of Law No. 6/2014 appointment of village apparatus should be consulted with the Regional Administrator given on behalf of the Bupati/Mayor and the constraining factors both experienced by the Village Government and the Village Applicant candidate is the lack of public awareness that the community has not served as Village Government itself, the level of education of Human Resources (HR), age, fees for file management, and the socialization that was done only in certain areas.